(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This study delves into the impact of multilingual education on the acquisition of English language skills among primary school students, addressing the growing importance of English proficiency in global communication and academic achievement. As primary education forms the bedrock of linguistic development, understanding how multilingual approaches influence English language acquisition becomes crucial. The research employs a comprehensive mixed-methods approach, combining quantitative assessments of language proficiency through standardized tests with qualitative insights garnered from interviews and focus groups with educators and students.The quantitative analysis reveals a statistically significant improvement in students’ English language skills following exposure to multilingual education. This improvement spans both spoken and written English, indicating a robust correlation between multilingual instruction and enhanced proficiency levels. Qualitative findings complement these results by elucidating educators’ and students’ perceptions and experiences within multilingual educational environments. They highlight the benefits of integrating students’ native languages into English instruction, not only for facilitating comprehension and retention but also for nurturing cultural and linguistic identities.